Chaski, a novel Drosophila lactate/pyruvate transporter required in glia cells for survival under nutritional stress - María Graciela Delgado; Carlos Oliva; Estefanía López; Andrés Ibacache; Alex Galaz; Ricardo Delgado; L. Felipe Barros; Jimena Sierralta (2018)
The intercellular transport of lactate is crucial for the astrocyte-to-neuron lactate shuttle (ANLS), a model of brain energetics according to which neurons are fueled by astrocytic lactate. In this study we show that the Drosophila chaski gene encodes a monocarboxylate transporter protein (MCT/SLC16A) which functions as a lactate/pyruvate transporter, as demonstrated by heterologous expression in mammalian cell culture using a genetically encoded FRET nanosensor. chaski expression is prominent in the Drosophila central nervous system and it is particularly enriched in glia over neurons. chaski mutants exhibit defects in a high energy demanding process such as synaptic transmission, as well as in locomotion and survival under nutritional stress. Remarkably, locomotion and survival under nutritional stress defects are restored by chaski expression in glia cells. Our findings are consistent with a major role for intercellular lactate shuttling in the brain metabolism of Drosophila.